Thermophysical properties of concentrated aqueous solution of N-methyldiethanolamine (MDEA), piperazine (PZ), and ionic liquids hybrid solvent for CO2 capture - Khan, S.N. (Elsevier B.V., 2017)
In the present study, thermophysical properties such as density, refractive index, surface tension, and viscosity of the concentrated aqueous solution of N-methyldiethanolamine (MDEA), piperazine (PZ), and ionic liquids (ILs) 1-butyl-3-methylimidazolium trifluoromethanesulfonate bmimOTf, 1-butyl-3-methylimidazolium acetate bmimAC were investigated. All the properties were measured at atmospheric pressure and temperature ranging from (298.15–343.15) K, with a regular interval of 5 K. The concentrations of N-methyldiethanolamine (MDEA) and piperazine (PZ) were kept constant at 30 and 3 wt%, respectively, while the concentration of ionic liquids bmimOTf, bmimAC were varied between 5 and 20 wt%. All the properties under investigation demonstrated their significant dependence on temperature and ionic liquid concentration. Increasing temperature showed decreasing trend of density, viscosity, refractive index, and surface tension of the hybrid solvents. Except for surface tension, density, refractive index, and viscosity were increased by increasing the concentration of ionic liquid in the hybrid solvents. Surface tension data were decreased with an increase in the concentration of ionic liquids at a constant temperature. The thermophysical properties of concentrated aqueous solution of hybrid solvents were correlated using an empirical correlations approach with respect to temperature and concentration. A good agreement was found between the correlated and experimental data at all conditions. © 2016 Elsevier B.V.